Developments for multiple-reflection time-of-flight mass spectrometers and their application to high-resolution accurate mass measurements of short-lived exotic nuclei - Ayet San Andres, Samuel; Justus Liebig University Giessen (My University, 2018)
In the context of this work, improvements and developments for Multiple-Reflection Time-of-Flight Mass-Spectrometers (MR-TOF-MS) have been developed for the measurement of exotic nuclei, enabling mass measurements of the most exotic and short-lived nuclei with the highest and unprecedented accuracy. The kinetic energy of the ions and the repetition rate of the spectrometer were increased, obtaining resolving powers in excess of 600.000 in less than 20 ms of measurement time and repetition rates exceeding 1000 Hz. In addition, an increase of the reliability and stability of the system, lowering the temperature coefficient of the spectrometer to 8 ppm/°C, has been shown. The system is universal and can measure elements independent of their chemical properties, demonstrated by measuring noble gases and very reactive elements like uranium. Moreover, the data analysis procedure to determine the mass value and the uncertainty was further improved. The method was specially developed to precisely extract the masses of very low statistics peaks and of overlapping peaks when only a change in peak shape can be observed. With this data analysis procedure, the effective mass resolving power is increased by up to a factor of 3 for overlapping peaks, e.g. the resolution of low-lying isomers.During three experiments at GSI (Germany) in 2014 and 2016, mass measurements of thermalized fission fragments of 238U as well as thermalized projectile fragments of 238U and 124Xe, produced and separated in the FRS, were performed with the MR-TOF-MS of the FRS-Ion Catcher with resolving powers up to 450.000. Following the improved data analysis procedure presented in this work, a total of 25 masses of short-lived nuclei were measured, of which 7 correspond to isomeric states with excitation energies down to about 280 keV. Isotopes of 8 different elements with half-lives of less than 300 ms have been measured. The reported masses obtained in this thesis with the MR-TOF-MS of the FRS-Ion Catcher have a minimum total relative uncertainty of 1.1·10-7, corresponding to an abosolute value of 13 keV. The lowest uncertainty of a mass measurement performed with at the FRS-Ion Catcher with the improvements presented in this thesis is 6·10-8 (Hornung, 2018). The average deviation from the literature of all the measured masses in the FRS-Ion Catcher is of 4.2 $pm$ 6 keV, showing no systematic deviation. Besides direct mass measurements, the broadband capabilities of the system in combination with a high resolving power were used for the identification via mass measurements of uranium ions and molecules in different charge states. This feature was applied to the study of the cleanliness of the system. The FRS-Ion Catcher is now fully operational and offers a superior combination of performance characteristics for measurements with exotic nuclei in unknown territory.In an experiment at TRIUMF (Canada) in 2017, mass measurements of neutron-rich gallium isotopes from A = 80 to A = 85 were performed with the newly installed TITAN´s MR-TOF-MS, developed, built and commissioned at the Justus-Liebig University. Recently the electronics have been improved in the same way as for the MR-TOF-MS at FRS/GSI. The masses of 84Ga and 85Ga, with half-lives of 85 ms and 92 ms, respectively, were measured for the first time in the context of this thesis. A minimum relative uncertainty of 3.3·10-7 was obtained. The mass measurements of 84Ga and 85Ga have a high impact on the understanding of the nucleosynthesis processes in the neutron star merger event observed by LIGO/VIRGO and followed by a blue kilonova transient, as they pin down the nuclear physics input for 82Se which can only be produced in the r-process.

Im Rahmen dieser Arbeit wurden Verbesserungen und Entwicklungen für Multireflexions Flugzeit-Massenspektrometer (MR-TOF-MS) entwickelt und für Massenmessungen von exotischen und kurzlebigen Kernen mit höchster und bisher unerreichter Genauigkeit benutzt. Die kinetische Energie der Ionen und die Wiederholungsrate des Spektrometers wurden erhöht. Eine Auflösung von mehr als 600000 in weniger als 20 ms Messzeit und Wiederholungsrate über 1000 Hz wurden erreicht. Darüber hinaus wurde die Zuverlässigkeit und Stabilität des Systems verbessert, was sich durch eine Reduktion des Temperaturkoeffizienten des Spektrometer auf 8 ppm/°C zeigt. Das System ist universell und kann Massen von Elementen unabhängig von ihren chemischen Eigenschaften messen, was durch die durchgeführte Messung von Edelgasen und sehr reaktiven Elementen am Beispiel von Uran gezeigt wurde. Außerdem wurde die Datenauswertemethode zur Bestimmung der Masse und ihrer Genauigkeit weiter verbessert. In drei Experimenten an der GSI Helmholtzzentrum für Schwerionenforschung GmbH in Deutschland wurden in den Jahren 2014 und 2016 Massen von themalisierten Spaltfragmenten von 238U sowie themalisierten Projektilfragmenten von 238U und 124Xe erzeugt und getrennt im Fragment Separator (FRS), mit dem MR-TOF-MS des FRS-Ion Catcher mit Auflösungen bis 450000 gemessen. Mit der verbesserten Datenauswertemethode wurden Isotope von acht verschiedenen Elementen mit Halbwertszeiten von weniger als 300 ms gemessen, insgesamt 25 Massen kurzlebiger Kerne, darunter sieben in isomeren Zuständen mit Anregungsenergien bis zu 280 keV. Die in dieser Arbeit mit den FRS-Ion Catcher erhaltenen Massen haben eine relative Genauigkeit von bis zu 1.1·10-7, was einem absoluten Wert von 13 keV entspricht. Die niedrigste bisher mit den FRS-Ion Catcher erreichte relative Genauigkeit beträgt 6·10-8. Die durchschnittliche Abweichung aller im FRS-Ion Catcher gemessenen Massen im vergleich mit Literaturwerten beträgt 4.3 $pm$ 2.5 keV und zeigt keine systematische Abweichung. Die Breitbandfähigkeiten des Systems in Kombination mit einem hohen Auflösungsvermögen wurden für die Identifizierung von Uranionen und Molekülen in verschiedenen Ladungszuständen durch Massenmessungen verwendet. Der FRS-Ion Catcher ist damit voll funktionsfähig und bietet eine hervorragende Kombination von Leistungsmerkmalen für Messungen mit exotischen Kernen in unbekanntem Gebiet.In einem Experiment am Canada´s National Laboratory for Particle and Nuclear Physics (TRIUMF) in Kanada wurden im Jahr 2017 mit dem neu installierten MR-TOF-MS von TRIUMF´S Ion Trap for Atomic and Nuclear Science (TITAN), das an der Justus-Liebig Universität Gießen entwickelt, gebaut und in Betrieb genommen wurde, Massenmessungen von neutronenreichen Galliumisotopen von A = 80 bis A = 85 mit einer relativen Genauigkeit von bis zu 3.3·10-7 durchgeführt. Die Elektronik wurde in gleicher Weise verbessert wie für das MR-TOF-MS beim FRS an der GSI. Die Massen von 84Ga und 85Ga mit Halbwertszeiten von 85 ms bzw. 92 ms wurden im Rahmen dieser Arbeit erstmals gemessen. Der Einfluss beider Massen auf die Nukleosynthese im schwacher r-Prozess wurde untersucht.
Entwicklungen für Multireflexions Flugzeit-Massenspektrometer (MR-TOF-MS) und ihre Anwendung zu hochauflösenden Massenmessungen von exotischen und kurzlebigen Kernen
Keywords: ddc:530